Incidence of lymph node metastasis at each station in Siewert types Ⅱ/Ⅲ adenocarcinoma of the esophagogastric junction: A systematic review and meta-analysis. (December 2020) - Chen, Xiao-Dong; He, Fu-Qian; Chen, Mi; Zhao, Fa-Zhi
Abstract: The optimal extent of lymphadenectomy for adenocarcinoma of the esophagogastric junction (AEG) has been continuously debatable. The study aimed to determine the incidence of lymph node metastasis at each station in Siewert types Ⅱ/Ⅲ AEG. PubMed was searched and publications reporting metastasis at each nodal station were eligible. Meta-analysis was performed using RevMan 5.3. Twenty-one studies involving 4662 patients were included. The incidence of lymph node metastasis was high (≥20%) in stations No. 3, 1, 2 and 7 in decreasing order, and moderate (10–20%) in stations No. 9, 19 and 110. The incidence did not exceed 10% in stations No. 10, 11p, 20, 8a, 4sa, 4 s b and 4d, was less than 5% in stations No. 5, 6, 11d, 12a, and even close to 0 in stations No. 107, 111 and 112. Compared with type Ⅲ tumors, type Ⅱ tumors had significantly lower incidence in some abdominal stations including No. 3, 4sa, 4 s b, 6, 8a and 10, while significantly higher in the lower mediastinal stations. The present analysis established a map of lymph node metastasis in Siewert types Ⅱ/Ⅲ AEG, which may serve as a valuable reference for the extent of lymphadenectomy. Highlights: AEG is a challenging surgical problem with an increasing incidence. Many aspects of the surgical treatment for AEG have not yet been resolved. A map of nodal metastasis may serve as a valuable reference for lymphadenectomy.